Dual character of peroxymonosulfate oxidation process to treat salty wastewater containing 2, 4, 6-tribromophenol. Issue 4 (August 2020) - Fang, Changling; Lou, Xiaoyi; Tang, Yunyu; Tian, Liangliang; Cai, Youqiong; Xiao, Dongxue; Guo, Yaoguang; Liu, Jianshe
Graphical abstract: Highlights: Cl − efficiently enhanced oxidative degradation of TBP by PMS. Unexpected halogenated organics were identified during the degradation of TBP. Time-dependent transformation of TBP by PMS/Cl − process was investigated. Consider first before treating salty TBP wastewater by PMS oxidation process. Abstract: Nowadays, increasing attention has been paid on the peroxymonosulfate (PMS) in situ oxidation for environmental decontamination. Chloride ion (Cl − ) could directly react with PMS to produce some reactive halogen agents via non-radical pathways. In present study, the degradation kinetics of 2, 4, 6-tribromophenol (TBP) and the total organic carbon (TOC) removal by adding PMS in salty wastewater were inspected. TBP could effectively degraded by PMS in salty wastewater over the pH range of 3.0−7.0, and the degradation ratio increased with the pH of reaction solution. Positive effects of Cl − concentration (1−100 mM) on TBP degradation kinetics were also examined. Moreover, the oxidation products and their evolution with reaction time were conducted in order to further evaluate the environmental benefits with co-existence of PMS and Cl − . Instead of complete mineralization, TBP was mainly transformed to new halogenated products which also have long half-lives. The chlorination of TBP is the dominant pathway in the presence of Cl −, since the main oxidant (HOCl) played an important role. The formation of undesirable halogenated products provides that adding PMS into salty wastewater might not be an unexpected proposal for TBP depletion involving of the attendance of chloride.